RAMIA (ANTI-ANEMIA TEENAGERS) PODCAST THROUGH YOUTUBE SOCIAL MEDIA AFFECTS ON TEENAGER GIRLS KNOWLEDGE AND ATTITUDES ABOUT ANEMIA AT JUNIOR HIGH SCHOOL 19 BENGKULU CITY - Reka Lagora Marsofely; Anisa Marsela; Wisuda Andeka Marleni (Poltekkes Kemenkes Bengkulu, 2023)
Anemia is one of the global health problems, particularly in developing countries. Young women are a group that is prone to anemia because they menstruate every month. Lack of information and knowledge about anemia can cause decreased body immunity, impaired learning concentration, academic achievement, adolescent fitness, and adolescent work productivity. One way to increase knowledge and attitudes is by promoting health through podcast media. This study is about the influence of podcasts through YouTube social media in increasing the knowledge and attitudes of young women about anemia. This research was conducted with a Pre-Experimental design with pre-test and post-test. The number of respondents was 33; the sampling technique was purposive. The intervention was done through podcasts with as many as three episodes, each lasting 8 minutes. The research instruments were questionnaires on knowledge and attitudes regarding anemia and original videos of researchers. The normality test is the Shapiro-Wilk test; the data is not normally distributed. The analysis continued using the Wilcoxon test with an ? < of 0.05. The results stated that the average value of knowledge and attitudes about anemia before and after the intervention increased (p-value 0.000). Health education through video podcasts increases knowledge (9.00) and attitudes (33.70). Video podcasts can increase teenagers' knowledge and attitudes about anemia. Hopefully, this video podcast can be used as an educational tool about anemia for young women.